Solution-processed flexible paper-electrode for lithium-ion batteries based on MoS2 nanosheets exfoliated with cellulose nanofibrils. (1st March 2019) - Cao, Shaomei; Shi, Liyi; Miao, Miao; Fang, Jianhui; Zhao, Hongbin; Feng, Xin
Abstract: In this article, a flexible free-standing MoS2 based paper-electrode for lithium-ion batteries (LIBs) was assembled according to a solution-based papermaking process and subsequent in situ carbonization. The ultrathin MoS2 nanosheets as active materials were efficiently exfoliated from bulk counterparts using TEMPO-oxidized cellulose nanofibrils (CNF) as assistant agents. Meanwhile, the oxidized CNF was utilized both as biobased binder and fibrous skeletons for the fabrication of hierarchical MoS2 hybrid films. The MoS2 based nanoarchitectures were finally achieved with carbon nanotubes (CNTs) as conductive fillers and further in situ carbonized under argon atmospheres. The in situ carbonization improved the electrical conductivity and specific surface area dramatically. The flexible paper-electrode assembled with ultrathin MoS2 nanosheets, carbonized CNF (C-CNF) and CNTs exhibited enhanced performance with a high specific capacity, nice rate capability, and long time cycling stability. The carbonized MoS2 /CNF/CNTs hybrid film can directly act as an ideal paper-electrode for LIBs without using traditional metallic current collector makes it appropriate for the next-generation flexible/wearable electronics in future. Graphical abstract: Carbonized MoS2 nanosheets/cellulose nanofibrils hybrid films with enhanced conductivity can be directly used as ideal paper-electrode for LIBs without metallic current collectors.